Enhanced Discrete-Time Differentiators for LCL Resonance Damping Through Capacitor Voltage Feedback - Olímpio Filho, José de Arimatéia; Silva, Paulo Fernando; de Oro Arenas, Luis; Curi Busarello, Tiago Davi; Godoy Simões, Marcelo; Morales Paredes, Helmo Kelis (IEEE, 2026)
The capacitor current active damping method is widely used to dampen the LCL-ﬁlter resonance in grid-connected inverters due to its simple implementation. Alternatively, it can be replaced by the capacitor voltage active damping (CVAD) as a low-cost solution, utilizing the capacitor voltage of LCL-ﬁlter for synchronization and damping, avoiding an extra sensor. A critical part of CVAD is the differentiator that is used to estimate capacitor current, yet, differentiators bring challenges due to their sensitivity to noise. To address these challenges, this article proposes a family of enhanced discrete-time differentiators —Lanczos, Super Lanczos 1, and Super Lanczos 2—for CVAD. This class of discrete-time differentiators based on ﬁnite impulse response ﬁlters is discussed, with detailed explanations provided on how to obtain the coefﬁcients of the differentiators. The system was implemented using controller hardware-in-the-loop and experimental results demonstrate the effectiveness of the proposed method in damping the LCL resonance in a single-phase grid-connected inverter under steady state, under reference step conditions, and in the presence of noise.
Keywords: Filters; Frequency; Noise; Current; Damping; Voltage; Timing; Capacitors; Inverters; Active damping (AD); capacitor voltage; digital differentiator; LCL-filter; fi=Sähkötekniikka|en=Electrical Engineering|